2004
DOI: 10.1002/hyp.5574
|View full text |Cite
|
Sign up to set email alerts
|

The episodic acidification of a stream with elevated concentrations of dissolved organic carbon

Abstract: Organic acids are generally thought to play a minor role in the episodic acidification of streams in the USA. In this study, we investigated the episodic acidification of a stream at the Hubbard Brook Experimental Forest in New Hampshire with high concentrations of dissolved organic carbon and naturally occurring organic acids. We studied three events in 2001: spring snowmelt, which occurred from 6 April to 14 May and resulted in two distinct melt events; and two rain events, one on 17 June and the other on 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 43 publications
(47 reference statements)
3
38
1
Order By: Relevance
“…The percentage of DOC exported during events from the forested watershed studied here was 86%, which can thus be viewed as a conservative estimate of the allochthonous/terrestrial contribution to stream DOC export from small (\100 km 2 ) forested watersheds without wetlands. Although the importance of hydrologic events to DOC flux has been demonstrated before (Ciaio and McDiffett 1990;Denning et al 1991;Murdoch and Stoddard 1993;Brown et al 1997;Hinton et al 1998;Volk et al 2002;Even et al 2004;Wellington and Driscoll 2004;Inamdar et al 2006;Saunders et al 2006), this study shows that events dominate DOC flux from forested end-member watersheds on a regional scale. Calculations based on Eq.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The percentage of DOC exported during events from the forested watershed studied here was 86%, which can thus be viewed as a conservative estimate of the allochthonous/terrestrial contribution to stream DOC export from small (\100 km 2 ) forested watersheds without wetlands. Although the importance of hydrologic events to DOC flux has been demonstrated before (Ciaio and McDiffett 1990;Denning et al 1991;Murdoch and Stoddard 1993;Brown et al 1997;Hinton et al 1998;Volk et al 2002;Even et al 2004;Wellington and Driscoll 2004;Inamdar et al 2006;Saunders et al 2006), this study shows that events dominate DOC flux from forested end-member watersheds on a regional scale. Calculations based on Eq.…”
Section: Discussioncontrasting
confidence: 53%
“…The important contribution of precipitation and snowmelt events to total annual DOC export has been documented (Ciaio and McDiffett 1990;Brown et al 1997;Hinton et al 1998;Volk et al 2002;Even et al 2004;Wellington and Driscoll 2004;Inamdar et al 2006;Saunders et al 2006), and recent observations indicate that the chemical composition and reactivity of soil-water and streamwater DOC changes markedly during rainfall and snowmelt (Easthouse et al 1992;Buffam et al 2001;Kaushal and Lewis 2003;Dalzell et al 2005Dalzell et al , 2007Volk et al 2005;Hood et al 2006;Vidon et al 2008). Although it is evident that hydrologic events (i.e., rainfall, snowmelt) serve as ''hot moments'' for the loss of labile carbon, organic-bound nutrients, and DOCassociated pollutants from the terrestrial landscape (McClain et al 2003), quantitative linkages between event-based DOC concentrations and stream discharge and other watershed characteristics have not been well elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of storm events on surface water acidification or other changes in solute chemistry may vary with event size, season, and antecedent moisture conditions. Wellington and Driscoll (2004) found that events following wet conditions produced more severe acid episodes than events following drier conditions. Biron et al (1999) studied solute concentrations during a sequence of fall storms for 2 years with contrasting moisture regimes and found that concentrations during the drier year were higher than those during the wetter year.…”
Section: Introductionmentioning
confidence: 96%
“…Nitrate export from diffuse sources (Burns et al, 1998;Boesch et al, 2001;Rabalais, 2002;De Vries et al, 2003) is a major cause of eutrophication and episodic acidification for inland aquatic systems and coastal zones (Vitousek et al, 1997;Crimo and McDonnell, 1997;Creed and Band, 1998;Galloway et al, 2003;Meader and Goldstein, 2003;Wellington and Driscoll, 2004). Resolving nutrient leaching rates of various diffuse sources may help watershed sustainability management maintaining required water quality and maximizing agricultural activity for food production.…”
Section: Introductionmentioning
confidence: 99%